PRESCRIBING PATTERN OF ANTIHYPERTENSIVE DRUGS IN ESSENTIAL HYPERTENSION IN MEDICINE OUT PATIENTS DEPARTMENT IN A TERTIARY CARE HOSPITAL - Konwar, Mahanjit; Kumar Paul, Pranab; Das, Swarnamoni (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To study the prescribing pattern of antihypertensive drugs in essential hypertension in medicine out patients department in a tertiary care hospital, Dibrugarh Methods: A retrospective observational study of 6 months duration was undertaken in the Medicine OPD. The prescriptions prescribed to the patients suffering from essential hypertension were collected and assessed. Parameters noted were: (1) number of antihypertensive agents used (2) the pattern of different groups of antihypertensive agents. Results: Out of 270 patients, 190 received monotherapy in which calcium channel blockers[CCB] (65%) is the most commonly used drugs followed by Angiotensinogen converting enzyme [ACE] inhibitors(14%), angiotensinogen receptor blocker [ARB] (12%), diuretics (6%), Î²-blockers (3%). The combination therapy comprises 80 (28%) prescription in which 64 (80%) received two drugs and 16(20%) received three drug combination. CCB + diuretics (30%) is the most commonly prescribed followed by ACE inhibitor + diuretics (20%) ARB + diuretics,(15%), ARB + Î²-blocker 5%, ARB + CCB (5%) and CCB + Î²- blockers (5%). In triple drug regime ACE inhibitors + diuretics + Î²- blocker (10%) and ARB + diuretics + Î²-blocker (10%) were used. Conclusion: The present study shows CCB is commonly used on account of its fewer side effects. The combination therapy is seen commonly in patients who come for follow up not being controlled by monotherapy. Key words: essential hypertension, prescription and antihypertensive drugs